ITSBAT TALAK DALAM PERSPEKTIF HUKUM PERKAWINAN DI INDONESIA - Zainuddin, Zainuddin; Khairina, Khairina; Caniago, Sulastri (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2019)
This study discusses about itsbat talak (legal recognition of divorce) pronounced by husbands out of court in the perspective of Marriage Law in Indonesia. There are three issues answered in this study. First, how is the legal problem of out-of-court divorce in the perspective of Marriage Law in Indonesia and Fiqh? Second, what is the urgency of itsbat talak in the view of fiqh and Marriage Law in Indonesia? Third, what is the review of the Marriage Law in Indonesia on the itsbat talak out-of-court? To answer this problem, a library study was conducted. The data was collected through searching of the research results, books, fiqh books, laws or regulations and electronic as well as digital data through websites. The study found that there are some legal problems of itsbat talak for out-of-court divorce such as its legality, the probability of talak for twice, no legal protection, the couple blocked from other marriage, and the lost of post-marriage rights. Itsbat talak for out of court divorce can be recognized in the Marriage Law in Indonesia. Studi ini mengkaji tentang itsbat (pengakuan hukum) talak yang telah dijatuhkan suami di luar pengadilan dalam perspektif hukum perkawinan di Indonesia. Ada tiga persoalan yang akan dijawab dalam studi ini. Pertama, bagaimana problematika hukum talak di luar pengadilan dalam perspektif Hukum Perkawinan di Indonesia dan Fikih ? Kedua, bagaimana urgensi itsbat talak dalam pandangan Fikih maupun Hukum Perkawinan di Indonesia ? Ketiga, bagaimana tinjauan Hukum Perkawinan di Indonesia terhadap itsbat talak  perceraian di luar pengadilan ? Untuk menjawab permasalahan ini dilakukan studi kepustakaan. Data tentang talak di luar pengadilan atau itsbat nikah dikumpul melalui penelusuran hasil-hasil penelitian, buku-buku atau kitab fikih, undang-undang atau peraturan dan data elektronik melalui website. Data ini diolah, dianalisis dan dijadikan bahan untuk mengkaji itsbat talak dengan menggunakan metode kajian hukum normatif. Hasil penelitian menemukan jawaban, pertama; ada lima problem hukum talak di luar pengadilan, seperti keabsahannya, kemungkinan terjadi talak dua kali, tidak adanya perlindungan hukum, pasangan talak di luar pengadilan tidak dapat melakukan penikahan resmi dengan yang lain, tidak bisa mendapatkan  hak-hak setelah talak. Itsbat talak dapat diakui dalam hukum perkawinan di Indonesia.